The complete plastome sequence from the family Malpighiaceae, Bunchosia argentea (Jacq.) DC - Sangjin Jo; Young-Kee Kim; Se-Hwan Cheon; Ki-Joong Kim (Mitochondrial DNA. Part B. Resources, 2019)
In this study, we determined the complete plastome sequence of Bunchosia argentea (Jacq.) DC. (Malpighiaceae) (NCBI acc. no. MK390344). The gene order and the structure of the B. argentea plastome are collinear with those of the typical plastomes of land plants. The complete plastome size is 158,741 bp in length and consists of a large single-copy region of 88,345 bp and a small single-copy region of 16,816 bp, which are separated by a pair of 26,790 bp-long inverted repeat regions. The overall A-T content of the plastome sequence is 63.5%. The plastome contains 110 genes, of which 76 are protein-coding genes, 30 are tRNA genes, and four are rRNA genes. The rpl32 was lost and two genes (infA and rps7) were pseudogenized. Sixteen genes contain one intron and two genes have two introns. A total of 87 simple sequence repeat loci were identified within the genome. Phylogenetic analysis revealed that B. argentea and two Byrsonima species formed a clade with 100% bootstrap support.